2012
DOI: 10.1590/s1984-29612012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis on the perceptions of milk producers about Rhipicephalus (Boophilus) microplus control in Minas Gerais

Abstract: Milk producers in Lavras, Passos and Divinópolis, Minas Gerais, were interviewed with the aim of evaluating their perceptions and attitudes regarding control over Rhipicephalus (Boophilus) microplus. Multivariate correlation between the variables was done by means of principal component analysis. The producers' perceptions and attitudes regarding R. (B.) microplus were similar: most of them did not have any basic knowledge of tick biology or control, and they applied acaricide products through backpack sprayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…These facts strengthen our hypothesis that climate conditions influence the detection of pyrethroid residues in bulk milk tank probably as a result of the subjective use of pyrethroids mainly based on observation of infestation levels (Rocha et al, 2012) and the influence of climate conditions on infestation by ectoparasites (Estrada-Peña et al, 2006;Paim et al, 2011). With this in mind, Souza et al, (1988) described that lower infestation levels of Rhipicephaus (Boophilus) microplus, the major ectoparasite in cattle (Raynal et al, 2013), occurred during months (i.e.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These facts strengthen our hypothesis that climate conditions influence the detection of pyrethroid residues in bulk milk tank probably as a result of the subjective use of pyrethroids mainly based on observation of infestation levels (Rocha et al, 2012) and the influence of climate conditions on infestation by ectoparasites (Estrada-Peña et al, 2006;Paim et al, 2011). With this in mind, Souza et al, (1988) described that lower infestation levels of Rhipicephaus (Boophilus) microplus, the major ectoparasite in cattle (Raynal et al, 2013), occurred during months (i.e.…”
Section: Resultssupporting
confidence: 84%
“…Thus, considering that climate conditions influence infestation by insects and ticks, such as horn flies (Haematobia irritans) and Rhipicephalus (Boophilus) microplus (Souza et al, 1988;Barros, 2001;Estrada-Peña et al, 2006;Paim et al, 2011), and the fact that the use of pyrethroids is mainly based on the subjective observation of infestation levels (Rocha et al, 2012), it was hypothesized that some climate condition parameters were associated with the occurrence of pyrethroid residues in bulk milk tank. For this reason, data on climate influences in pyrethroid residues in raw milk are of great relevance, particularly in tropical climate countries as Brazil, where different conditions of rainfall, relative humidity and temperature are perceived on unequable basis (Picinin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Rocha et al (2012) most of the interviewees had only reached elementary school level (54%), but this did not show any correlation with the efficiency of tick control. However, Santos et al (2009), in the State of Rio Grande do Sul, observed that illiterate farmers, or the ones only with elementary school level, presented a threefold greater chance of failure in tick control procedures than farmers with higher education level.…”
Section: Discussionmentioning
confidence: 83%
“…The months during which the dairy cows experienced increased infestation by insects and ticks, such as horn flies (Haematobia irritans) and Rhipicephalus (Boophilus) microplus, coincided with the time period that the cows primarily remained on the pasture (Estrada-Peña et al, 2006). Because treatment with pyrethroids is mainly based on the subjective observation of infestation levels, treatment of these animals is typically increased (Da Rocha et al, 2012) in months when cows remained on the pasture. A positive relationship between milk lactose and energy balance has been proposed, suggesting that milk lactose concentrations are affected by energy balance (Schei et al, 2005;Beerda et al, 2007;Ouweltjes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%